Effectiveness of commonly used disinfectants in hospitals against common nosocomial bacteria - Mim, Maisha Hossain (Brac University, 2024)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Biotechnology and Bachelor of Science in Microbiology, 2023.